Effect of phosphor sedimentation on photochromic properties of a warm white light-emitting diode *Project supported by the National Natural Science Foundation of China (No. 11474036), the Natural Science Foundation of Shanghai (No. 12ZR1430900), the Shanghai Institute of Technology Talents Scheme (No. YJ2014-04), the Shanghai Municipal Alliance Program (Nos. Lm201514, Lm201505, Lm201455), the Science and Technology Commission of Shanghai Municipality (CN) (No. 14500503300), Shanghai Cooperative Project (No. ShanghaiCXY-2013-61), and Jiashan County Technology Program (No. 20141316). (December 2018) - Zhuang, Yunyi; Wang, Yong; Wang, Liping; Li, Zhanguo; Li, Wenbo; Yang, Lei; Zou, Jun
Abstract: In the process of producing a white light emitting diode, the consistency of the optical coherence and stability of the photochromic properties is a crucial index for measuring the quality of the product. Phosphor sedimentation is a significant factor affecting optical coherence, thus, in this paper, seven sets of control experiments were set up with the phenomenon of the phosphor precipitation at time intervals 0, 2, 5, 10, 20, 30, and 40 min. The color coordination concentration and optical properties were also tested. The results indicate that phosphor sedimentation occurs between 0 and 20 min, during which the color coordinate placement is concentrated, the central coordinates are ( x = 0.4432 ± 0.004, y = 0.4052 ± 0.002); the quality was verified because the supply demand chain management (SDCM) was no greater than 7. Later, between 30 and 40 min, the central coordinates are ( x = 0.4366 ± 0.003, y = 0.4012 ± 0.003), which had an SDCM value higher than 7, and had a more discrete color placement; it does not meet the requirements of the national standard GBT24823-2016 general lighting LED module performance.